IMPLEMENTASI DISIPLIN GURU SD DALAM MENTAATI PERATURAN DISIPLIN - Iman Teguh (Jurnal Hukum, 2019)
This research methodology uses the approach of juridical sociology with descriptive of research type. The method of collecting data uses observation and interview. The method of analyze data uses qualitative description. The results of the research are: 1) the implementation of elementary school teacher’s discipline to obey the roles of discipline state officer at UPPK Taman Dinas Pendidikan, Pemuda dan Olah raga in Pemalang regency, namely the application of the government role number 53 on 2010 about discipline state officer, and the role of Pemalang regent number 26 on 2012 about the day and work-time of the state officers at Pemalang regency. 2) The problem which the implementation of elementary school teacher’s discipline to obey the roles of discipline state officer made is that not all the elementary school teachers obey the roles of discipline state officer about work-time of state officer. 3) The solution for solving the problem which the implementation of elementary school teacher’s discipline to obey the roles of discipline state officer made namely: a) Specific socialization of the roles of discipline state officer and work time is needed. b) Intensive monitoring of the roles of discipline and work time for state officer should be done. c) The firm sanction for the elementary school teachers who break the roles of discipline state officer should be given. d) The day and the work time of the elementary teachers should be revised become flexible work time so that the teachers can do their duties without breaking the role of state officer discipline, especially on the role of the state officer work-time.